Managing Central Nervous System Spread of Lung Cancer: The State of the Art. Issue 6 (20th February 2022) - Tsui, David Chun Cheong; Camidge, D. Ross; Rusthoven, Chad G.
Abstract : Brain metastases (BrM) are common in both non–small-cell lung cancer and small-cell lung cancer. Substantial progress in BrM management has occurred in the past decade related to advances in both radiation and medical oncology. Recent and ongoing radiation trials have focused on increasing the candidacy for focal therapy of BrM with stereotactic radiosurgery; reducing the toxicity and improving patient selection for whole brain radiotherapy; and, in small-cell lung cancer, evaluating brain magnetic resonance imaging surveillance without prophylactic cranial irradiation, hippocampal avoidance in prophylactic cranial irradiation and whole brain radiotherapy, and the role of upfront stereotactic radiosurgery for BrM. In medical oncology, the development of multiple tyrosine kinase inhibitors with encouraging CNS activity and emerging data on the CNS activity of immune checkpoint inhibitors in some patients have opened the door to novel systemic and multidisciplinary treatment strategies for the management of BrM. Future research will focus on more robust characterizations of the CNS activity of targeted therapy and immunotherapies, as well as optimal integration and patient selection for multidisciplinary strategies involving CNS-active drugs, radiation therapy, and CNS surveillance.